2012
DOI: 10.1186/1756-0500-5-189
|View full text |Cite
|
Sign up to set email alerts
|

A small scale study on the effects of oral administration of the β-glucan produced by Aureobasidium pullulans on milk quality and cytokine expressions of Holstein cows, and on bacterial flora in the intestines of Japanese black calves

Abstract: BackgroundThe β–(1 → 3),(1 → 6)-D-glucan extracellularly produced by Aureobasidium pullulans exhibits immunomodulatory activity, and is used for health supplements. To examine the effects of oral administration of the β–(1 → 3),(1 → 6)-D-glucan to domestic animals, a small scale study was conducted using Holstein cows and newborn Japanese Black calves.FindingsHolstein cows of which somatic cell count was less than 3 x 105/ml were orally administered with or without the β-(1 → 3),(1 → 6)-D-glucan-enriched A. pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
2
8
0
1
Order By: Relevance
“…Therefore, it is assumed that the orally administered AP-CF constitutively activate the immunity by daily feedings. Our previous study using cattle suggested that the beneficial effects of the A. pullulans -cultured fluid on the health including the activation of immune system would appear after the long-term administration under conventional condition [48] . Although the properties of the effects of long-term administration of AP-CF on the immune system might be distinct from that of the short-term administration, the immunostimulating effects of AP-CF are not thought to be disappeared after the long-term administration.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is assumed that the orally administered AP-CF constitutively activate the immunity by daily feedings. Our previous study using cattle suggested that the beneficial effects of the A. pullulans -cultured fluid on the health including the activation of immune system would appear after the long-term administration under conventional condition [48] . Although the properties of the effects of long-term administration of AP-CF on the immune system might be distinct from that of the short-term administration, the immunostimulating effects of AP-CF are not thought to be disappeared after the long-term administration.…”
Section: Discussionmentioning
confidence: 99%
“…Additional study found different effects based on type and purity of glucan used. Both glucans increased the feed uptake, but differed in modulation of immune responses [ 40 ].…”
Section: Glucans In Pig Immunitymentioning
confidence: 99%
“…On the other hand, β-glucans from mycelium biomass contained in the pretreated residue can be an additional glucose source in the rumen or replace part of the carbohydrates, hemicellulose, and cellulose, which are degraded by the fungus [10]. β-glucans from other types of fungal organisms like yeast have also shown their nutritional functions when added to feed as presented in [39] for the case of Holstein cows and Japanese black calves; the orally administered β-(1→3),(1→6)-D-glucan may affect the growth of particular bacterial strains, which are able to use it as a nutrient, and this may influence the formation of bacterial microbiota in the intestine. In addition, the increasement of glucanases activity may affect oligosaccharides and glycoproteins production from feed in the rumen.…”
Section: Introductionmentioning
confidence: 99%